CONCENTRATIONS OF Cr, Cu AND Zn IN THE SHELLFISH CLAM (Meretrix meretrix) FROM THE COASTAL WATERS SEI NAGALAWAN SERDANG BEDAGAI REGENCY NORTH SUMATRA PROVINCE - Aritonang, Desy Novela; Amin, Bintal; Nedi, Syahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted on February 2018 by taking samples of M.meretrixin the coastal waters of Sei Nagalawan, Serdang Bedagai Regency in North Sumatra Province. This research aims to know the heavy metal content of Cr, Cu, and Zn on shellfish M. meretrixwith different size, to evaluate the difference between the stations, and relationship between the content of heavy metals with the size of the mussels, as well as to analyze the feasibility of the consumption of shellfish M. meretrix. The highest content of Cr (10,787 µg/g) wasfound in the small size in the station 1. The highest content of Cu (2,240 µg/g) was found in the medium-size at Stations 3. The highest Zn content (70,493 µg/g)was found in the medium-size at Stations 2. The value of Metal Pollution Index (MPI) for SeiNagalawancoastal waters is classified in the category of 9.03. The safe limit the consumption of shellfish M. meretrixbased on the value of the PTWI illustrates that mussels originating from the coastal waters of SeiNagalawan still eligible for consumption, as long as it doesn't exceed the limits of safe consumption are already determined. Key Words : Heavy Metals, Pollution, North Sumatra, Meretrix meretrix